Analyzing the components and applications of wireless sensor network: a concise study - Lu Fan (Big Data and Computing Visions)
Wireless Sensor Networks (WSNs) consist of small nodes with identifying component by sensing, computation, and wireless communications infrastructure capabilities. The path searching means routing, power management, and data dissemination protocols have been specifically designed for WSNs where energy awareness is an essential design issue. Routing protocols in WSNs might differ depending on the application and network architecture. WSN provide several types of applications providing comfortable and smart-economic life. The easy molding, fault tolerance, high sensing fidelity, low price, and rapid deployment features of sensor networks create various new and thrilling application areas for remote sensing. In future, this wide range of application areas will make sensor networks an important part of our lives. However, understanding of sensor networks needs to satisfy the constraints presented by factors such as fault tolerance, scalability, cost, hardware, dynamic topology, environment, and power consumption.